Perancangan User Interface / Experience Aplikasi ABC Menggunakan Metode Kansei Engineering - Anwar, Faris Asiful; Sodik, Anwar (Institut Teknologi Adhi Tama Surabaya, 2025)
This study aims to improve the quality of the user interface (UI) and user experience (UX) of the ABC application using the Kansei Engineering approach. Through data collection from 30 respondents, multivariate statistical analysis such as Coefficient Correlation Analysis, Principal Component Analysis, and Partial Least Square were used to translate user emotions into design elements. The results of the study produced design recommendations based on the concept of the emotion